Inflammatory Signaling Networks as Targets for Pharmacological Intervention of Chronic Diseases - Maitra, Urmila; Baglin, Samantha M.; Li, Liwu (Current Signal Transduction Therapy, 2009)
Inflammatory signaling networks play critical roles in the interpretation and processing of external and internal challenges encountered by living organisms. Consequently, alterations in various inflammatory processes are linked with almost all human diseases, and provide important clues for potential pharmacological intervention. Macrophages and CD4 T helper cells are central modulators within the inflammatory network. Both cells can adopt distinct phenotypes and activation status depending upon their environments. Consequently, they are critically involved in the progression as well as attenuation of various inflammatory processes. This review will highlight recent progress in our understanding toward the complex activation and differentiation of macrophages and CD4 T helper cells and their involvement in inflammation. Furthermore, we will discuss potential cellular and molecular targets within the inflammatory network for pharmacological intervention of human inflammatory diseases.
Keywords: inflammatory diseases